2001
DOI: 10.1097/00005537-200111000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Videostroboscopic Images in Presbylarynges

Abstract: Bowing does not consistently predict the extent of glottal gap. Therefore, other presbylaryngeal changes are probably contributing to incomplete glottal closure, which are not well-visualized stroboscopically, so the finding of bowing is not sufficiently specific to identify presbylarynges. The significantly smaller normalized laryngeal outlet values suggest that this identifies a compensatory strategy for glottal gap to optimize vocal function. This is a novel finding that contrasts with medial ventricular fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 21 publications
2
86
0
7
Order By: Relevance
“…In particular, older adults had lower minimum, maximum and mean f0 and amplitude SD values compared with younger adults for sustained vowels, but similar f0 and amplitude SD values compared with younger adults for connected speech. Because speech fundamental frequency is due to the physiological characteristics of the vocal folds and control of the larynx musculature (Honjo and Isshiki 1980;Bloch and Behrman 2001;Baken 2005;Sato et al 2011), the absence of change observed in mean and range speech fundamental frequency here suggests that the state of the tissue and general motor control did not deteriorate with age (at least in the age range studied), or did not deteriorate enough to have a functional impact. These results indicate that, while sustained vowel production was affected negatively by age, connected speech was less vulnerable to age.…”
Section: Connected Speechmentioning
confidence: 74%
See 1 more Smart Citation
“…In particular, older adults had lower minimum, maximum and mean f0 and amplitude SD values compared with younger adults for sustained vowels, but similar f0 and amplitude SD values compared with younger adults for connected speech. Because speech fundamental frequency is due to the physiological characteristics of the vocal folds and control of the larynx musculature (Honjo and Isshiki 1980;Bloch and Behrman 2001;Baken 2005;Sato et al 2011), the absence of change observed in mean and range speech fundamental frequency here suggests that the state of the tissue and general motor control did not deteriorate with age (at least in the age range studied), or did not deteriorate enough to have a functional impact. These results indicate that, while sustained vowel production was affected negatively by age, connected speech was less vulnerable to age.…”
Section: Connected Speechmentioning
confidence: 74%
“…In particular, physiological changes occur in the larynx (Honjo and Isshiki 1980;Bloch and Behrman 2001;Ximenes Filho et al 2003;Kersing and Jennekens 2004;Pontes et al 2005Pontes et al , 2006Sato et al 2010Sato et al , 2011, the vocal tract (Pontes et al 2006), and the respiratory system (Linville 1996;Teles-Magalhães et al 2000;Ramig et al 2001;Sauder et al 2010). These changes include calcification and ossification of cartilages, muscles and vocal fold atrophy, vocal fold bowing (i.e., inward curve) and reduced mucosal wave, and reduced pulmonary lung pressures, volumes, elasticity, and recoil.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar das manifestações do envelhecimento laríngeo serem bastante individuais, são comuns a presença de saliência dos processos vocais, do arqueamento de pregas vocais, da fenda glótica durante fonação (PONTES; BRASOLOTTO;BEHLAU, 2005;YAMASAKI;BEHLAU, 2006;SANTOS, 2011;YAMAUCHI et al, 2015), além de constrição supraglótica (HAGEN; LYON; NUSS, 1996;BLOCH;BEHRMAN, 2001;YAMASAKI;BEHLAU, 2006;STAGER;BIELAMOWICZ, 2010). Frente às alterações decorrentes do envelhecimento das estruturas responsáveis pela fonação, é comum ocorrerem alterações vocais.…”
Section: Lista De Ilustraçõesunclassified
“…Dentre as características laríngeas do idoso, a região supraglótica, frequentemente apresenta-se com aumento de volume das pregas vestibulares durante a respiração e movimento de constrição mediana e/ou anteroposterior durante a fonação (HAGEN;LYON;NUSS, 1996;BLOCH;BEHRMAN, 2001;YAMASAKI;BEHLAU, 2006;STAGER;BIELAMOWICZ, 2010). Estes aspectos são considerados como reações compensatórias ao fechamento glótico insuficiente durante a fonação e diversas abordagens terapêuticas para presbifonia, têm o objetivo de melhorar o fechamento glótico e reduzir a constrição supraglótica (LAGORIO; CARNABY-MANN;CRARY, 2010;GODOY, 2016).…”
Section: Lista De Ilustraçõesunclassified
See 1 more Smart Citation